Authentication of isolated hydroxychavicol from p. Betle linn. Leaves using nuclear magnetic resonance spectroscopy - Ab. Hadi, Hazrina; Azmar, Hawa Mas (2016)
Introduction: Nuclear magnetic resonance (NMR) spectroscopy is an analytical chemistry technique used for the chemical structural determination. This valuable tool is used to study nuclei, commonly hydrogen (1H) and carbon (13C). NMR provides information about the number of atoms of the studied nuclei that are magnetically separated as well as the nature of the environment of the nuclei. Aims: In this study, NMR is used to identify the isolated hydroxychavicol. The isolated hydroxychavicol was dissolved in deuterated methanol. Methods: The sample is analyzed for 1D NMR (1H and 13C) spectra using 500 MHz NMR (Bruker; Avance III Ultrashield Plus; Switzerland) located in Universiti Malaysia Pahang. The target directed isolation of hydroxychavicol was performed by comparing bioautographic profile of hydroxychavicol-rich fraction to that of hydroxychavicol standard. Hydroxychavicol is a known compound with molecular formula of C9H10O2 and molecular weight of 150.174 g/mol. Results and discussion: 1H and 13C NMR elucidated the structure of the isolated hydroxychavicol. The 1H NMR spectrum furnished 10 protons at chemical shifts of δH 3.21, 4.90, 4.98, 5.9, 6.49, 6.61, and 6.67 ppm. Based on the spectrum, a broad spectrum was displayed meaning there is a hydroxyl group in the structure. The 13C NMR spectrum displayed the nine carbons at chemical shifts δC 40.64, 115.33, 116.31, 116.76, 120.87, 132.99, 139.57, 144.46, and 146.17 ppm. Conclusion: The isolated hydroxychavicol was successfully being authenticated by NMR.